2006
DOI: 10.1016/j.physbeh.2006.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in blood glucose levels under hyperinsulinemia affect accumbens dopamine

Abstract: Dopaminergic systems have been implicated in diabetes and obesity. Notwithstanding, the most basic relationship between dopamine and plasma insulin as well as glucose levels yet remains unknown. The present experiments were designed to investigate the effects of acute hyperinsulinemia on basal dopamine levels in the nucleus accumbens of the rat under chloral hydrate anesthesia using acute microdialysis in combination with the hyperinsulinemic-glycemic clamping procedure. In Experiment 1, each rat was infused w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…This is in keeping with previous findings where hypoglycemia increased dopamine release in the region [47] and 2DG evoked c-Fos in neurons in the area [4] although, a reduced dopamine turnover [48] has also been reported. Our data also support the idea that Ser31 activity is related to dopamine turnover in the brain [15].…”
Section: Discussionsupporting
confidence: 93%
“…This is in keeping with previous findings where hypoglycemia increased dopamine release in the region [47] and 2DG evoked c-Fos in neurons in the area [4] although, a reduced dopamine turnover [48] has also been reported. Our data also support the idea that Ser31 activity is related to dopamine turnover in the brain [15].…”
Section: Discussionsupporting
confidence: 93%
“…However, as we did not find a significant RH treatment effect on mPFC dopamine on either days of testing, our data suggest that some other neurochemical system may underlie the effects of RH on set-shift performance, rather than dopamine. Consistent with this, one previous study has suggested that dopamine release (albeit under different conditions) is unaffected by alterations in brain glucose metabolism that persist for up to 80 minutes [54]. …”
Section: Discussionsupporting
confidence: 75%
“…The striatum (i.e, the NAcc) contains neurons that sense glucose [88], expresses insulin receptors [89] and insulin action in the brain provides a negative feedback signal [90]. Moreover, insulin modulates dopamine signaling effectively reducing reinforcement potency [91, 92]. In humans, reduced insulin sensitivity is associated with less endogenous dopamine at D2/3 receptors in the NAcc and acute dopamine depletion, in turn, reduces insulin sensitivity [93].…”
Section: Endocrine Modulation Of Dopamine Signalingmentioning
confidence: 99%